Performance and Analysis of a Novel Grain Dryer with ANN Controller - C Maheswara Reddy , R Kiranmayi (International Journal of Advanced Science and Technology, 2020)
Grain drying used to store grains for future purpose by maintaining parameters like Temperature, moisture content etc., with suitable conditions. This creates quality and novelty in grains. For this, we are proposed ANN controller this replaces the GOFIP controller. The drawback of GOFIP controller more settling sampling number required to reach the target value of system, by using ANN controller we are reduced sampling number to reach the target value, Peak over shoot, and provided the good anti disturbances rejection. The ANN controller designed by using the function fitting neural network model from the MATLAB.